Assessing Organizational Maturity in a University-Based Da'wah Technology Center: An Organizational Maturity Index Approach - Evi Septiani Tavip Hayati; Euis Marlina (Perkumpulan Ahli Manajemen Dakwah Indonesia (PAMDI), 2026)
Purpose – This study evaluates the Center for Da'wah Technology Development (Pusat Pengembangan Teknologi Dakwah/PPTD) of the Faculty of Da'wah and Communication's organizational maturity in supporting student competency development using the Organizational Maturity Index (OMI). Design/methodology/approach – This study uses a quantitative survey method with an OMI-based questionnaire to measure six main dimensions of organizational maturity, namely: Management Process, Leadership and Strategy, Risk Management, Resource Management, Culture and Employee Development, and Performance Measurement and Evaluation. Respondents consisted of 49 active PPTD members with varying lengths of involvement Findings – The results show that PPTD has a relatively high average maturity level (3.9), with the highest score in the Culture and Employee Development dimension (4.2), indicating a collaborative and innovative environment. However, there is a gap between the actual conditions and the respondents' expectations in the aspects of Risk Management and Performance Measurement, with a gap value of 1.1. Respondents also expect improvements in technology, facilities, and intensive training. Research implications – These results indicate that although PPTD has advanced in several aspects of organizational maturity, there is an urgent need to improve the performance evaluation system, ensure adequate budget allocation, strengthen risk mitigation, and allocate resources to enhance the organization's resilience and effectiveness. The implication of this study is the importance of PPTD investing in technology and strengthening its culture of innovation to achieve higher operational efficiency and organizational resilience in the face of the challenges of the digital era. Originality/value – This study is among the first to apply the Organizational Maturity Index (OMI) to a university-based da'wah technology center within an Islamic higher education context. It extends the use of OMI beyond business organizations and highlights how organizational maturity can be developed in a resource-limited yet innovation-driven environment. The findings provide a valuable reference for similar educational and faith-based organization